Understanding the Influence of Parental Involvement on Youth Sports Experiences within a Youth Sports Systems Framework - Raspati, Ramadisa Nuki; Pitriani, Pipit; Rismayadi, Alen (Universitas Pendidikan Indonesia, 2025)
The youth sports system is a complex ecosystem involving various stakeholders, including coaches, teammates, sports organizations, and parents. Parental involvement should not be viewed in isolation but in relation to other elements within this system. For example, parent-coach interactions can influence the motivational climate, which shapes young athletes' perceptions and behaviors. Moreover, individual factors such as parents’ beliefs and values toward sports impact how they engage in their children’s athletic experiences. Excessive expectations may create pressure and reduce enjoyment, while supportive parenting is linked to greater intrinsic motivation and satisfaction in youth. Adolescents’ developmental stages also play a critical role. As adolescents undergo physical, cognitive, and psychosocial changes, their needs and responses to parental involvement evolve. Older adolescents may seek greater autonomy, requiring parents to adjust their involvement accordingly. This literature review aims to synthesize research on parental involvement in youth sports, considering the dynamic interactions between parents, adolescents, coaches, and sports organizations. By integrating developmental and contextual perspectives, this review seeks to offer a comprehensive understanding of how parental involvement shapes youth sports experiences. The findings are expected to inform best practices that support positive youth development through appropriately tailored parental engagement in sports.